Suberoylanilide hydroxamic acid sensitizes neuroblastoma to paclitaxel by inhibiting thioredoxin‐related protein 14‐mediated autophagy. Issue 7 (19th June 2017) - Zhen, Zijun; Yang, Kaibin; Ye, Litong; You, Zhiyao; Chen, Rirong; Liu, Ying; He, Youjian
Abstract : Paclitaxel is not as effective for neuroblastoma as most of the front‐line chemotherapeutics due to drug resistance. This study explored the regulatory mechanism of paclitaxel‐associated autophagy and potential solutions to paclitaxel resistance in neuroblastoma. The formation of autophagic vesicles was detected by scanning transmission electron microscopy and flow cytometry. The autophagy‐associated proteins were assessed by western blot. Autophagy was induced and the autophagy‐associated proteins LC3‐I, LC3‐II, Beclin 1, and thioredoxin‐related protein 14 (TRP14), were found to be upregulated in neuroblastoma cells that were exposed to paclitaxel. The inhibition of Beclin 1 or TRP14 by siRNA increased the sensitivity of the tumor cells to paclitaxel. In addition, Beclin 1‐mediated autophagy was regulated by TRP14. Furthermore, the TRP14 inhibitor suberoylanilide hydroxamic acid (SAHA) downregulated paclitaxel‐induced autophagy and enhanced the anticancer effects of paclitaxel in normal control cancer cells but not in cells with upregulated Beclin 1 and TRP14 expression. Our findings showed that paclitaxel‐induced autophagy in neuroblastoma cells was regulated by TRP14 and that SAHA could sensitize neuroblastoma cells to paclitaxel by specifically inhibiting TRP14. Abstract : The paclitaxel‐induced autophagy in neuroblastoma cells is regulated by TRP14. The TRP14 inhibitor SAHA sensitizes neuroblastoma cells to paclitaxel in vitro .